ANALYTIC HIERARCHY PROCESS FOR EVALUATION OF TRANSPORTATION ALTERNATIVES ON THE KARKH SIDE OF BAGHDAD - Maryam M. Abdullah; Noor M. Asmael (Journal of Engineering and Sustainable Development, 2023)
The Analytical Hierarchy Process (AHP) is a mathematical method which is considered This method is considered one of the most accurate methods in terms of making decisions by providing multiple options so that the decision-maker can calibrate and evaluate the alternatives. The city of Baghdad suffers from stifling traffic congestion due to the increase in population, which leads to a significant increase in the number of trips inside and outside the city, and with this, the number of vehicles is more than the capacity of the city’s road network; especially on the Karkh side. Three alternative roads were proposed in the network; namely: the first alternative is the fourth ring road that connects the Abu Ghraib highway and the roundabout bridge, the second road represents the link between the Washash roundabout and the Muthanna Airport intersection, the third alternative is constructing a tunnel from the Al-Paratha Mosque intersection in the direction of Haifa Street. The purpose of the study is to analyze and select the best alternative by using multi-criteria decision-making. Based on the results, it appears that the economic factor has the greatest effect on the selection of alternatives with its weight equal to 55%, followed by the accessibility factor with a weight of 29.8%. Although the second alternative was chosen as the best alternative in this manuscript, the first alternative is also important in terms of reducing traffic congestion and truck crossing within the city. To increase the efficiency of the network, it is proposed to implement the first and second proposals as well as widen the study region.